Cotyledon peeling method for passion fruit protoplasts: a versatile cell system for transient gene expression in passion fruit (Passiflora edulis) - Wang, Linxi; Liu, Haobin; Liu, Peilan; Wu, Guanwei; Shen, Wentao; Cui, Hongguang; Dai, Zhaoji (Frontiers in Plant Science, 2023)
Passion fruit (Passiflora edulis) is a perennial evergreen vine that grows mainly in tropical and subtropical regions due to its nutritional, medicinal and ornamental values. However, the molecular biology study of passion fruit is extremely hindered by the lack of an easy and efficient method for transformation. The protoplast transformation system plays a vital role in plant regeneration, gene function analysis and genome editing. Here, we present a new method ('Cotyledon Peeling Method') for simple and efficient passion fruit protoplast isolation using cotyledon as the source tissue. A high yield (2.3 × 10 7 protoplasts per gram of fresh tissues) and viability (76%) of protoplasts were obtained upon incubation in the enzyme solution [1% (w/v) cellulase R10, 0.25% (w/v) macerozyme R10, 0.4 M mannitol, 10 mM CaCl2, 20 mM KCl, 20 mM MES and 0.1% (w/v) BSA, pH 5.7] for 2 hours. In addition, we achieved high transfection efficiency of 83% via the polyethylene glycol (PEG)-mediated transformation with a green fluorescent protein (GFP)-tagged plasmid upon optimization. The crucial factors affecting transformation efficiency were optimized as follows: 3 μg of plasmid DNA, 5 min transfection time, PEG concentration at 40% and protoplast density of 100 × 10 4 cells/ml. Furthermore, the established protoplast system was successfully applied for subcellular localization analysis of multiple fluorescent organelle markers and protein-protein interaction study. Taken together, we report a simple and efficient passion fruit protoplast isolation and transformation system, and demonstrate its usage in transient gene expression for the first time in passion fruit. The protoplast system would provide essential support for various passion fruit biology studies, including genome editing, gene function analysis and whole plant regeneration.